LOCALIZATION OF HUMAN RESOURCES MANAGEMENT IN MULTINATIONAL COMPANIES - Liao Yanting; Mahlia Muis; Wardhani Hakim (Transpublika Publisher, 2023)
This article discusses the importance and implementation strategies of human resource localization management in multinational corporations. The localization of human resources is to adapt to the local environment and cultural differences, and to improve employee motivation and loyalty. The implementation of localization management needs to pay attention to the needs of the local market, establish a localization team, formulate recruitment and training plans, and pay attention to labor relationship management. Multinational companies should realize the key role of localization management in successfully entering the local market, and constantly optimize their strategies to adapt to the changing global environment.